An aqueous one-pot route to gold/quantum rod heterostructured nanoparticles functionalized with DNA. Issue 89 (22nd September 2015) - Hamon, C.; Martini, C.; Even-Hernandez, P.; Boichard, B.; Voisin, H.; Largeau, L.; Gosse, C.; Coradin, T.; Aimé, C.; Marchi, V.
Abstract : We report an original approach exploiting the photoelectrochemical properties of quantum rods and the versatility of Au(I) organometallic chemistry to control DNA surface grafting. Abstract : We report an original approach exploiting the photoelectrochemical properties of quantum rods and the versatility of Au(i ) organometallic chemistry to control DNA surface grafting. This one-pot aqueous approach provides Janus biofunctionalized nanoparticles, the assembly of which should results in the emergence of synergistic properties.